On the distribution of Gaussian primes (London Journal of Research In Science: Natural and Formal, 2023)
In this paper, we will first explore the distribution of Gaussian primes in the first quadrant locally and, furthermore, use the findings to investigate the distribution of Gaussian primes on a wide variety of straight lines.
Keywords: sustainability; conservation; nature architecture; khasi; jaintia; ficus elastica; Modeling.; Well-Log Controlled; Seismic Attribute; Reservoir Pore-fill Interpretation